Is climate emergency a war or are we uprooting the system? Framing conceptual metaphors in the climate emergency discourse - Ribeiro, Camila Belizário (Redis: Revista de Estudos do Discurso, 2022)
The visible worldwide consequences of climate change have triggered countless public debates among scientific communities from several knowledge areas, raising public awareness to this issue. Rhetoric and discourse strategies have played a crucial role on how global warming cannot be ignored, thereby instigating policymakers to implement urgent action to reduce CO2 emissions and other causes of environment degradation. Thus, the present paper aims at dissecting a brief corpus of Instagram posts from two renowned environmental activist entities, the NGO Fridays for Future and Greta Thunberg, with the purpose of identifying new metaphorical representations in the multimodal youth climate activism, alongside with other social aspects involved in this rhetoric. For that goal we chose the hashtag #Uprootthesystem, currently adopted by some environmental activists who believe that the climate crisis narrative makes room for other historical reparation discourses, arguing against colonization, poverty, discrimination, racism, class inequality, climate injustice, among others.